2022
DOI: 10.1002/ehf2.14055
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognostic implications of reduced left ventricular ejection fraction among patients with STEMI in India

Abstract: AimsTo describe clinical characteristics and outcomes for those with STEMI and reduced left ventricular ejection fraction (LVEF) in low-income and middle-income countries (LMICs). Methods and resultsAdults presenting with STEMI to two government-owned tertiary care centres in Delhi, India were prospectively enrolled in the North India ST-elevation myocardial infarction (NORIN-STEMI) registry. LVEF was evaluated at presentation and clinical characteristics were compared across LVEF categories. Overall, 3597 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…This is in accordance with research conducted by Fraticelli et al with BMI  25[16]. Risk factors such as smoking, hypertension, DM and dyslipidemia were also identified as causes of STEMI in line with previous findings by Hendrickson 2022 and Fraticelli 2020[15,16].…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with research conducted by Fraticelli et al with BMI  25[16]. Risk factors such as smoking, hypertension, DM and dyslipidemia were also identified as causes of STEMI in line with previous findings by Hendrickson 2022 and Fraticelli 2020[15,16].…”
supporting
confidence: 92%
“…. Other research conducted by Hendrickson et al also obtained the age of STEMI patients 55 years[15]. In gender, the majority of STEMI patients are male.…”
mentioning
confidence: 92%
“…Whilst on the other hand, LVEF > 40%, use of aspirin, beta blockers, ACEi/ARBs significantly favored survival in this cohort of patient. Lower LVEF is already an established risk factor for higher mortality as reported by sub analysis of NORIN-STEMI registry 27 . Cardiogenic shock, reported in up to 10% of STEMI patients, carries high mortality rates of around 40% at 30 days and 50% at one year 28 .…”
Section: Discussionmentioning
confidence: 88%
“…Timely identification of subjects at risk for HF development using a multimodality approach and early initiation of guideline-directed HF therapy in these patients can decrease the HF burden [ 13 ]. Previous studies had confirmed that age, delayed presentation, previous history of myocardial infarction, atrial fibrillation, hyperlipidaemia, renal impairment, anterior localization of AMI and proximal lesion location were the risk factors of LVSD in STEMI patients [ 14 18 ]. And some markers, such as peak CK, B-type natriuretic peptide, fasting blood glucose, stress marker total thiol groups, and fibrosis marker HE-4 had been confirmed to be associated with rLVEF after STEMI [ 19 – 21 ].…”
Section: Discussionmentioning
confidence: 99%